Pendidikan Antikorupsi Sebagai Upaya Preventif dalam Membangun Budaya Integritas - Abdillah Farel Leksono; Ihsan Akbar Aira Bintang (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Corruption remains a structural problem that hinders Indonesia's national development in economic, governance, and public trust dimensions. Law enforcement approaches alone have proven insufficient to significantly reduce corruption because they only address symptoms rather than the underlying weakness of individual integrity. This article aims to examine the role of anti-corruption education as a preventive strategy in building a culture of integrity among the younger generation and society at large. This study employs a literature review method by examining relevant journal articles, books, and prior research related to anti-corruption education and character development. The collected data were analyzed descriptively and qualitatively through content analysis to identify patterns, conceptual linkages, and strategic recommendations. The findings indicate that anti-corruption education, when consistently integrated into formal curricula, school culture, and family environments, can foster moral awareness, honesty, responsibility, and the courage to reject corrupt practices from an early age. However, implementation still faces challenges such as limited educator competence, insufficient role modelling, and suboptimal cross-sector involvement. This study recommends strengthening participatory learning approaches, leadership exemplars, and synergy among families, schools, government, and society so that a culture of integrity can grow sustainably.